Variation and Character Association for Various Pod Traits in Tamarindus indica L. - Divakara, B. N. (Indian Forester, 2008)
Tamarindus indica L. is an open-pollinated crop, hence improvement in the crop yield depends on the progress of variability in the desired characters in the base material vis-a-vis germplasm collection. An evaluation of thirty-five genotypes of tamarind was carried out based on variability and character association in various pod traits as a scope for further productivity improvement. Variability studies for pod traits revealed that, genotype TI-9 recorded maximum for seven traits viz. pod width (5.48 cm), pod thickness (2.43 cm), pulp weight (51.33 g), vein weight (4.15 g), shell weight (17.90 g), pod weight (83.06 g), and pulp per cent (61.42). However maximum pod length was recorded by the genotype TI-22 (26.60 cm). Genotype TI-26 exhibited the lowest for six traits viz. pod length (8.31 cm), seed weight (1.91 g), vein weight (0.20 g), shell weight (2.11g), pod weight (8.46 g) and pulp weight (4.23 g). Pod traits like shell weight, pod weight, pulp weight, and vein weight exhibited higher estimates of heritability coupled with higher genetic advance. Correlation coefficient studies indicated that pulp weight per pod expressed highest positive genotypic and phenotypic association with pod weight, vein weight, shell weight, pod width and pod length. Path coefficient analysis revealed that, pod weight, pulp per cent, seed per cent and shell per cent exhibited positive direct effect on pulp weight.